Adaptive Frequency Regulation of Doubly-Fed Pumped Storage Unit Considering Speed and Power Limit - LAO Wenjie, SHI Linjun, WU Feng, YANG Dongmei, LI Yang (Shanghai Jiaotong Daxue xuebao)
Doubly-fed pumped storage unit can adjust its power flexibly through variable-speed operation, enabling it to participate in the frequency regulation of the grid in both generating and pumping modes. To explore the frequency regulation capability of doubly-fed pumped storage unit, frequency regulation modules adapted to the characteristics of units under different operating conditions are built, and a frequency regulation strategy with adaptive variable parameters considering the speed and power limit of the unit is proposed. First, based on the dynamic model of the unit considering reversible pump turbine, the frequency regulation modules are built, in which the frequency deviation is converted to additional power command in generating mode but to additional speed command in pumping mode. Then, the impacts of control parameters on the frequency dynamic response are analyzed, and the calculation method of optimal frequency regulation parameters under multi conditions is proposed based on the improved particle swarm optimization algorithm, which aims at minimizing the frequency deviation and takes the speed and power limit of the unit as constraints. Based on the proposed method, an adaptive frequency regulation strategy is further presented in which frequency regulation parameters adjust with the change of operating conditions of the unit. Finally, a four-machine two-zone system model with doubly-fed pumped storage unit is built, and the simulation results show that the frequency regulation strategy proposed can make the unit achieve a great frequency regulation performance under different operating conditions.